2017
DOI: 10.3389/fbioe.2017.00009
|View full text |Cite
|
Sign up to set email alerts
|

Synergy Repetition Training versus Task Repetition Training in Acquiring New Skill

Abstract: Traditionally, repetitive practice of a task is used to learn a new skill, exhibiting as immediately improved performance. Research suggests, however, that a more experience-based rather than exposure-based training protocol may allow for better transference of the skill to related tasks. In synergy-based motor control theory, fundamental motor skills, such as hand grasping, are represented with a synergy subspace that captures essential motor patterns. In this study, we propose that motor-skill learning throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 44 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…The promoting training incorporating neuroplasticity principles, must be considered so that the performance capacity to perform dual tasks can be improved [ 25 ]. Using frequent and varied repetitions of different specific exercises is necessary for improving or maintaining performance [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The promoting training incorporating neuroplasticity principles, must be considered so that the performance capacity to perform dual tasks can be improved [ 25 ]. Using frequent and varied repetitions of different specific exercises is necessary for improving or maintaining performance [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since postural synergies of upper limb self-reaching movements were embedded in this exoskeleton's structure, the motions generated by the exoskeleton were in line with the natural movement characteristics of the human upper limb. Recent studies [42,43] have shown that postural synergy can improve the efficiency of motor learning for healthy volunteers. To our knowledge, this is the first time a postural synergy based rehabilitation exoskeleton robot has been introduced into rehabilitation training for stroke patients [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have shown that postural synergies can improve the efficiency of motor learning in healthy people [41][42][43] and that these synergies show great potential in the field of rehabilitation. To the authors' knowledge, currently, no synergy-based rehabilitation exoskeletons are used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Hassan et al [45] achieved postural synergy at the control level for gait reconstruction of the lower limb exoskeleton. Some recent studies have shown that postural synergies can improve the efficiency of motor learning in healthy people [46,47]. Although the design based on postural synergy may limit the overall capacity of the device and cause constraints, by limiting the reproduced tasks to ADL tasks and improving the design of the structure or controller, the human natural motion characteristics can be reproduced to the greatest extent, furthermore, since most stroke survivors exhibit pathological synergies, postural synergy-based rehabilitation robots may help overcome pathological synergies or compensatory motion, allowing patients to relearn normal characteristics of natural human movements [44].…”
Section: Introductionmentioning
confidence: 99%